Enhancing learning motivation through augmented reality: a study of Orang Asli children - Abd Rahim, Nur Aira; Borhan, Hafizzhal Bukhary (Macrothink Institute, 2025)
This study explores the use of Augmented Reality (AR) technology to enhance learning motivation among Orang Asli primary children in non-formal settings in Pahang, Malaysia. Through qualitative interviews with children and observations during engaging AR activities, the research examines how AR influences children's engagement, emotional responses, and motivation in learning. Findings indicate that AR fosters an interactive and immersive learning environment, significantly increasing children's emotional engagement and promoting real-world relevance in their learning experiences. The study highlights how AR technology can create a stimulating learning atmosphere that captivates children's attention and curiosity. Furthermore, the use of AR allows children to interact with educational content in innovative ways, helping them grasp complex concepts more easily. By connecting their learning to real-life situations, AR makes the content more meaningful and relatable. This study underscores the potential of AR as an effective educational tool, particularly in culturally diverse and marginalized communities. By integrating AR technology into educational practices, there is an opportunity to bridge gaps in traditional learning methods, enhance motivation, and ultimately improve educational outcomes for indigenous children in Malaysia. The findings contribute to the growing body of literature on technology-enhanced learning and its implications for educational equity.